Differential regulation of undecylprodigiosin biosynthesis in the yeast-scavenging Streptomyces strain MBK6 - Baral Bikash; Siitonen Vilja; Laughlin Mitchell; Yamada Keith; Ilomäki Mikael; Metsä-Ketelä Mikko; Niemi Jarmo (OXFORD UNIV PRESS, 2022)
Streptomyces are efficient chemists with a capacity to generate diverse and potent chemical scaffolds. The secondary metabolism of these soil-dwelling prokaryotes is stimulated upon interaction with other microbes in their complex ecosystem. We observed such an interaction when a Streptomyces isolate was cultivated in a media supplemented with dead yeast cells. Whole-genome analysis revealed that Streptomyces sp. MBK6 harbors the red cluster that is cryptic under normal environmental conditions. An interactive culture of MBK6 with dead yeast triggered the production of the red pigments metacycloprodigiosin and undecylprodigiosin. Streptomyces sp. MBK6 scavenges dead-yeast cells and preferentially grows in aggregates of sequestered yeasts within its mycelial network. We identified that the activation depends on the cluster-situated regulator, mbkZ, which may act as a cross-regulator. Cloning of this master regulator mbkZ in S. coelicolor with a constitutive promoter and promoter-deprived conditions generated different production levels of the red pigments. These surprising results were further validated by DNA-protein binding assays. The presence of the red cluster in Streptomyces sp. MBK6 provides a vivid example of horizontal gene transfer of an entire metabolic pathway followed by differential adaptation to a new environment through mutations in the receiver domain of the key regulatory protein MbkZ.